Entrepreneurs' Perceptions of the Role of Social Media in Increasing Business Competitiveness - Solihat, Asri; Isnawati, Isnawati; Adiansyah, Adi; Hamdani, Nizar Alam; Maulani, Galih Abdul Fatah; Nugraha, Sukma (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
The involvement of an active entrepreneurial community in utilizing social media can increase the effectiveness of the creative economy in the region. The purpose of this study is to analyze the use of social media to enable entrepreneurs to reach a wider audience. The research method uses a qualitative approach with a qualitative descriptive study design, sampling techniques in qualitative descriptive research often use purposive sampling. Data analysis techniques are carried out in a qualitative descriptive manner, prioritizing understanding meaning and phenomena rather than just measurement. The results of this study indicate that social media plays a role in increasing business competitiveness in the environment, social media has a complex role in improving the business sector of entrepreneurs. Social media as a tool, but a detailed understanding of how to use and design interactions is also needed to build strong relationships with consumers. Therefore, the wise use of social media can increase business competitiveness for the sustainability and growth of every entrepreneur's business.